2018
DOI: 10.1002/ece3.4278
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of a vector of human diseases: Aedes aegypti in its ancestral range, Africa

Abstract: Aedes aegypti, the major vector of dengue, yellow fever, chikungunya, and Zika viruses, remains of great medical and public health concern. There is little doubt that the ancestral home of the species is Africa. This mosquito invaded the New World 400‐500 years ago and later, Asia. However, little is known about the genetic structure and history of Ae. aegypti across Africa, as well as the possible origin(s) of the New World invasion. Here, we use ~17,000 genome‐wide single nucleotide polymorphisms (SNPs) to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(124 citation statements)
references
References 54 publications
10
113
0
1
Order By: Relevance
“…We also sequenced 9 previously collected individuals of the human-biting domestic form from Rabai 10 , which was not present when we carried out the fieldwork for this study in 2017. Analyses of overall population structure were consistent with earlier work 6,20 . The program ADMIXTURE 21 revealed strong support for a model with three genomic clusters or ancestry components corresponding to coastal East Africa, Central/West Africa, and globally invasive human specialists ( Fig.…”
Section: Preference For Humans Within and Outside Africa Has A Singlesupporting
confidence: 84%
See 1 more Smart Citation
“…We also sequenced 9 previously collected individuals of the human-biting domestic form from Rabai 10 , which was not present when we carried out the fieldwork for this study in 2017. Analyses of overall population structure were consistent with earlier work 6,20 . The program ADMIXTURE 21 revealed strong support for a model with three genomic clusters or ancestry components corresponding to coastal East Africa, Central/West Africa, and globally invasive human specialists ( Fig.…”
Section: Preference For Humans Within and Outside Africa Has A Singlesupporting
confidence: 84%
“…Host-seeking females take up to 95% of their blood meals from humans in nature 3 . This human-biting specialist is thought to have evolved from generalist ancestors in Africa approximately 5,000-10,000 years ago, possibly in northern Senegal or Angola 6,7 . However, in at least a few places in East Africa, the contemporary African subspecies Ae.…”
mentioning
confidence: 99%
“…FastStructure analysis revealed that the number of model components and model maximum likelihood were maximised by assigning each individual to between K4-6 populations. Similar to that reported previously, we find that the new world variation is composed of an admixture of populations distinct from African and Asian sources at higher values of K (19,20). Individuals from Panama, Costa Rica, Colombia, the Caribbean islands and populations from Arizona and Texas in South western USA were consistently composed of a similar composition throughout each possible value of K (SI Appendix Fig S1).…”
Section: Resultssupporting
confidence: 87%
“…Comparison of global population structure was achieved by comparing a subset of 2,630 of our SNP's from Panama that were shared with a previously acquired Ae. aegypti SNP dataset from 26 other countries worldwide (19)(20)(21)(22)(23). FastStructure analysis revealed that the number of model components and model maximum likelihood were maximised by assigning each individual to between K4-6 populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation